EVALUASI PRODUKSI BIOMASSA DAN KARAKTERISTK TAJUK Indigofera zollingeriana PADA JARAK TANAM YANG BERBEDA (Evaluation of biomass production and canopy characteristics of Indigofera zollingeriana on different plant spacing) - Desi Purnamasary Banurea; Luki Abdullah; Nur Rohmah Kumalasari (Buletin Ilmu Makanan Ternak, 2017)
Indigofera zollingeriana is a legume tree which has a high quality and production. This study was aimed to evaluate the biomass production and canopy characteristics of I. zollingeriana on different plant spacing. This study was arranged by the randomized block design on 4 different plant spacing, namely 1.0 m x 1.25 m, 1.0 m x 1.0 m, 1.0 m x 0.75m and 1.0 m x 0.50 m with four replications. The observed variables were canopy characteristics such as number of branch and twig, individual plant biomass production (fresh and dry weights), total production of steam and leaf, and ratio of stem to leaf. Plant spacing was significantly increased the number of branch, individual biomass production (fresh and dry weights), total production of steam and leaf, stem to leaf ratio (P<0.05). The average of branch and twig number ranged from (19-34) and (9-21), while the steam to leaf ratio was  less than 1. The highest production found at a plant spacing of 1.0 m x 1.25m was 5.09 kg/plant fresh weight or 1.29 kg/plant dry weight. It can be concluded that the plant spacing of 1.0 m x 1.5 m was the most ideal plant spacing to grow I. zollingeriana.Keywords. Plant spacing, biomass production, canopy, I. zollingeriana